Particles in drinking water - Luleå, Sweden - Ayisi Sarpong, Frederick (2007)
Achieving a comprehensive understanding of the solid particle content in raw and finished treated water provides a basis for continued improvements in water treatment processes and reduction in for example biological hazards. Most instrumentation used for particle analysis uses optical technology. In this thesis work, Multisizer™ 3 COULTER COUNTER® for particle counting, primarily based on light obscuration or scattering from individual particles, was adopted to investigate water quality by estimating particle numbers, sizes and distribution (in a range between 0.48 -60µm) of drinking water produced from Gäddvik Water Treatment plant at Luleå, Sweden. Size estimations of the particle counter were based on calibration with specific optical properties. To obtain a representative insight into particle composition, two sampling points were considered which were Gäddvik Water Treatment plant and Porsön residential area. Aspects of conductivity, pH and turbidity was also measured in the investigations and used as reference values. Three different studies of the water quality at these sampling points were conducted. The results showed that: 1. In Gäddvik, the average daily particle count (in the size range 0.48 - 12µm) in the treated water from the studied period was between 27000 to 30000 particles per ml, 2. The concentration of particles in the groundwater at Gäddvik, within the size interval 0.48- 12µm varies very much depending on from which well the water is measured, 3. Daily particle counts from 32000 to 45000 per ml for the 12- 24 hours of average water residence time usually occurred in the network connection system to Porsön residential areas, 4. There were rapid increases in particle concentrations commonly in the mornings and evenings of the weekdays and on weekends in Porsön residential areas. Generally, the water quality in respect to particle numbers are not the same in the pipe lines as in the treated water leaving the treatment plant. The particles both increase and decrease in numbers. The mean ...